OP0086 Long noncoding RNA H19X as a new therapeutic target for fibrosis. (15th June 2017) - Pachera, E; Wunderlin, A; Assassi, S; Salazar, G; Frank-Bertoncelj, M; Dobrota, R; Brock, M; Feghali-Bostwick, C; Rogler, G Gerhard; Dijkstra, G; Haaften, T van; Distler, J; et al.
Abstract : Background: Long noncoding RNAs (lncRNAs) are an emerging class of transcripts involved in the regulation of gene expression. We have recently identified a novel lncRNA, H19X, to be upregulated in systemic sclerosis (SSc). We also demonstrated that H19X is a key mediator of TGFβ-driven myofibroblast development and extracellular matrix synthesis. Objectives: To assess whether (1) H19X upregulation in SSc fibroblast is anti-apoptotic and pro-proliferative thereby favoring fibrosis (2) H19X is a regulator of fibrotic diseases in general. Methods: To study the function of H19X in apoptosis and proliferation of of dermal fibroblasts we silenced H19X using locked nucleic acid oligonucleotides (LNA GapmeRs followed by microarray analysis, qPCR, BrdU cell proliferation assay, Caspase 3/7 apoptosis assay and scratch assay. Cells were treated with 10 ng/ml TGFβ. Lung tissues were obtained from patients with SSc and idiopathic pulmonary fibrosis (IPF) undergoing transplantation, and from healthy controls (HC). Resected gut tissue from fibrotic and non-fibrotic areas was obtained from Crohn's disease patients. Non-cancer-affected gut tissue from resections because of adenocarcinoma was used as control. Expression of H19X was analyzed by quantitative (q)PCR. Results: H19X knockdown followed by microarray analysis (n=5) showed that FAS signaling pathway, cyclins and cell cycle regulation, regulation of cell cycle progression by Plk3, and free radical induced apoptosis were among the pathways with the highest number of significantly enriched genes (n=5; p<0.005). Apoptosis markers like BCL2, IGFBP3 and FAF1 (n=5, p<0.05) were upregulated in H19X-silenced fibroblasts. This indicated that targeting H19X might have a pro-apoptotic effect on fibroblasts thereby protecting from fibrosis. Functional studies showed enhanced fibroblast apoptosis after H19X silencing and TGFβ stimulation (n=5, p<0.05). In addition to decreased apoptosis, increased fibroblast proliferation might also favor fibrosis. Indeed, H19X downregulation led to reduced cell proliferation as measured by BrdU assay (n=5, p<0.05). Scratch assay (n=5) showed that H19X knockdown decreases TGFβ reduced wound healing. H19X expression was significantly increased in SSc interstitial lung disease and IPF patients versus HC (n=11 each, p<0.05). A significant H19X overexpression was also detected in fibrotic tissue from Crohn's disease patients (n=4–10, p<0.05). Conclusions: H19X supports TGFβ driven fibrosis not only by favoring myofibroblast development and extracellular matrix synthesis, but also by inducing proliferation and reducing apoptosis of dermal fibroblasts. These effects are not limited to SSc, but appear operative in a wider range of fibrotic diseases. Our results highlight the lncRNA H19X as a potent new therapeutic target in fibrotic diseases opening thereby new possibilities for the treatment of TGFβ driven fibrosis. Disclosure of Interest: E. Pachera: None declared, A. Wunderlin: None declared, S. Assassi Consultant for: Boehringer Ingelheim, Genentech and Biogen IDEC Inc., Bayer HealthCare, G. Salazar: None declared, M. Frank-Bertoncelj: None declared, R. Dobrota: None declared, M. Brock: None declared, C. Feghali-Bostwick: None declared, G. Gerhard Rogler: None declared, G. Dijkstra: None declared, T. van Haaften: None declared, J. Distler Shareholder of: 4D Science, Grant/research support from: from Anamar, Active Biotech, Array Biopharma, BMS, Bayer Pharma, Boehringer Ingelheim, Celgene, GSK, Novartis, Sanofi-Aventis, UCB, Consultant for: Actelion, Active Biotech, Anamar, Bayer Pharma, Boehringer Ingelheim, Celgene, Galapagos, GSK, Inventiva, JB Therapeutics, Medac, Pfizer, RuiYi and UCB., G. Kania Grant/research support from: Bayer, O. Distler Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, Pfizer, Sanofi, Consultant for: 4 D Science, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, ChemomAb, EpiPharm, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, Mepha, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Pfizer, Sanofi, Serodapharm, Sinoxa, Speakers bureau: AbbVie, iQone Healthcare, Mepha